LEKSIKAL PINJAMAN BAHASA ARAB PADA BAHASA GAYO (KAJIAN LEKSIKOLOGI) - Firdaus, Muhammad; Maulidati, Maulidati (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
This research examines the lexical borrowing originating from Arabic, which is productively used in the Gayo language. This article is expected to increase understanding of Arabic lexical borrowing in the Gayo language by applying a linguistic study approach to find Arabic loan lexical data in the Gayo language. Besides, the data obtained can also be used as one of the modern techniques used to improve the quality of learning Arabic by using Arabic loan words for teaching a second language. This article uses a qualitative analysis method based on discussion and comparison. In terms of sources, this article analyses the dictionary's contents as a study analysis unit to evaluate the assimilation of Arabic words according to word classification. From the data obtained, it was found that there was 397 Arabic loan lexical in the Gayo language, and there was a change in the phonological structure of the Arabic loan word elements in the Gayo language due to different spelling systems and phonological structural patterns between the two languages.